Novel Methods for Solving Linear and Nonlinear Integral Equations - Ray, Santanu Saha; Sahu, Prakash Kumar; Taylor and Francis (Boca Raton, FL : Chapman and Hall/CRC, 2018)
This book deals with the numerical solution of integral equations based on approximation of functions and the authors apply wavelet approximation to the unknown function of integral equations. The book's goalis to categorize the selected methods and assess their accuracy and efficiency.
Preface. Authors. Acknowledgement. Preliminary Concepts. Numerical Methods and Function Approximation. Numerical solutions of Fredholm integral equations by B-spline Wavelet Method. Numerical solutions of nonlinear Fredholm integral equations system by polynomial approximation and orthogonal functions. Numerical solutions of Hammerstein integral equations arising in Chemical phenomenon. Numerical solution of system of Volterra integro-differential equations. Numerical solutions of Volterra integro-di erential equation form of Lane-Emden type differential equations. Application of Legendre Spectral Collocation Method for solving integro-di erential equations. Numerical solutions of fuzzy integral equations. Numerical solutions of fractional integro-di erential equations. Bibliography. Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: MATHEMATICS / Differential Equations; MATHEMATICS / Number Systems; Integral equations -- Numerical solutions; Wavelets (Mathematics); Electronic books